Capturing dynamic conceptual frames - Urbaniak, Rafal (Logic Journal of IGPL, 2009)
The main focus of this paper is to develop an adaptive formal apparatus capable of capturing arguments conducted within a conceptual framework. I first explain one of the most recent theories of concepts developed by cognitivists, in which a crucial part is played by the notion of a dynamic frame. Next, I describe how a dynamic frame may be captured by a finite set of formulas and how a formalized adaptive framework for reasoning within a dynamic frame can be developed.